Kemiskinan, Ketidakadilan dan Pegiat Punk Sebagai Fringe Community di Era Globalisasi - Firdaus, Muhammad Jullyo Bagus (Global and Policy Journal of International Relations, 2019)
ABSTRACTThe presence of Globalization has produced dynamics in global issues. The emergence of poverty issues experienced by developing countries is due to economic globalization. Social inequalities experienced by third world countries, triggered because not all individuals are able to meet the needs of living standards. The emergence of globalization and economic liberalization provides the initial doctrine that will help economic integration between actors in international relations. The existence of liberalization and supported by globalization can not be separated about the existence of the doctrine of modernity. This will indirectly cause inequality and poverty. Explanation of the World System Theory provides an overview of the conditions experienced by the countries of the third world. This theory explains the existence of perceptions regarding the hemisphere north and south. Poverty and inequality experienced by third world countries due to exploitative actions from the core countries which are indirectly facilitated by globalization. In line with the development of globalization, in the process of introducing a marginalized group namely the fringe community, in this discussion discusses the band and connoisseurs of Punk music that has been getting negative stigma from the public. In various countries, especially starting in the 70s to the present, punk activists have had negative impacts such as violence and racism for the environment and society. al. Those who are in the social order by conveying messages through their work on the issue of poverty, inequality and also injustice in the social and global environment, although this has positive impacts, it can be a form of the wrong effort because of the violence they have committed. The shape of the emergence of their existence is certainly with the help of globalization. The form of resistance from punk activists to regimes in a country also has an impact on social movements that will change the social order in society. Given that the role of the state in the era of globalization is basically too small to solve big problems and too big to take care of small things.Keywords: Globalization, Injustice, Punk, Poverty, Fringe community DOI : https://doi.org/10.33005/jgp.v7i02.1828